2011
DOI: 10.7763/ijtef.2011.v2.120
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic of Current Account in Emerging East-Asian:Does Exchange Rate Matter?

Abstract: Abstract-The aim of this project is to study the dynamics of a country's current account with the change of currency exchange rate. This phenomenon becomes more significant when the 1997 financial crisis hits Southeast Asian countries like Malaysia, Indonesia, Singapore, Korea, Thailand and the Philippines. Collected data will be divided into two sub-periods, pre-and post-crisis. By method, the changes can be presented clearly and concretely. In addition, the method of Structural Vector Auto Regressive, SVAR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The result of GMM from 1973 to 2010 for the quarterly data of Thailand, the Philippines, Korea, and Indonesia showed differential impact due to frequent changes in policies. (Sek & Chuah, 2011), analysed current account concerning changes in exchange rate regimes from 1980Q1 to 2010Q4 for Thailand, Malaysia, Singapore, Korea, and the Philippines. They reveal that the current account is not affected due to changes in the exchange rate regime in the post-crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result of GMM from 1973 to 2010 for the quarterly data of Thailand, the Philippines, Korea, and Indonesia showed differential impact due to frequent changes in policies. (Sek & Chuah, 2011), analysed current account concerning changes in exchange rate regimes from 1980Q1 to 2010Q4 for Thailand, Malaysia, Singapore, Korea, and the Philippines. They reveal that the current account is not affected due to changes in the exchange rate regime in the post-crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many other studies (Miles, 1979; Rose, 1990; Sek and Chuah, 2011; Ball et al , 1977) advocated that currency devaluation does not affect current account or trade balance. Miles (1979) empirically found no evidence to support the argument that devaluation improves the trade balance both in the short and long run albeit the balance of payment seems to improve in the year following devaluation under the pooled cross-section time-series technique.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…As Senhadji and Montenegro (1998) stated, Africa has the lowest price and income elasticities reflecting the structure of the region’s main exports and imports. Sek and Chuah (2011) also examined the impact of exchange rate shock on the current account balance in ASEAN economies, and found that exchange rate has no impact on the current account balance during the post-crisis in all ASEAN economies except Malaysia. Rather, real current account shock and consumer prices are the main determinants of the current account balance.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…The similarity in the direction of exchange rate movement is also confirmed by the correlation values as shown in Table AI. One possible reason for the depreciation of currencies is persistent deficit on its current account (Sek and Chuah, 2011), as is shown in Table AII.…”
Section: Exchange Market Pressure Indexmentioning
confidence: 99%